2023
DOI: 10.3390/nu15092039
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Whey Protein Supplementation on Sarcopenia Progression among the Elderly: A Systematic Review and Meta-Analysis

Abstract: We conducted a systematic literature review and meta-analysis to investigate the role of whey protein supplementation in the functioning of the elderly with sarcopenia. The aim was to investigate the available scientific evidence and determine the best recommendations with respect to whey protein supplementation in sarcopenic patients. Methods: Databases, including CINAHL, Embase PubMed, and Web of Science, were searched from database inception until 31 December 2022 for randomised controlled trials (RCTs) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…However, recent review studies have indicated that protein supplementation alone may not lead to significant changes in parameters associated with sarcopenia [ 26 , 27 ], which contradicts the findings from previous studies [ 28 ]. On the other hand, a meta-analysis review has shown that exercise training alone or in combination with protein supplementation improved muscle mass, grip strength, reduced total fat mass, as well as waist circumference in individuals with sarcopenia [ 29 ].…”
Section: Introductionmentioning
confidence: 86%
“…However, recent review studies have indicated that protein supplementation alone may not lead to significant changes in parameters associated with sarcopenia [ 26 , 27 ], which contradicts the findings from previous studies [ 28 ]. On the other hand, a meta-analysis review has shown that exercise training alone or in combination with protein supplementation improved muscle mass, grip strength, reduced total fat mass, as well as waist circumference in individuals with sarcopenia [ 29 ].…”
Section: Introductionmentioning
confidence: 86%
“…Estes últimos não somente apoiam a síntese proteica, como também contribuem para a manutenção dos níveis de glicose sanguínea através de mecanismos que podem ou não envolver a insulina. Além disso, o whey protein é notável pela sua rica concentração de leucina, alta digestibilidade e rápida assimilação de aminoácidos, sugerindo um potencial benefício adicional no manejo da sarcopenia em idosos quando comparado à suplementação exclusiva de L-leucina (Kamińska, 2023).…”
Section: Introductionunclassified
“…It has also been proposed that priming the muscles with exercise prior to plant-based protein intake may overcome the muscle protein synthesis limitations described; meaning plant-proteins could be a good protein source when coupled with exercise, particularly in this vulnerable population [ 30 ]. However, previous systematic reviews have found that animal protein is still favourable over plant protein for both younger and older adults [ 31 , 32 ], and the majority of systematic reviews in this space have specifically targeted animal-based protein sources such as whey [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%